An inappropriate shock after reprogramming tachycardia zones - Rita Marinheiro; Leonor Parreira; Pedro Amador; Dinis Mesquita; Lurdes Almeida; Ana Lousinha; José Farinha; Marta Fonseca; Ana Fátima Esteves; Rui Caria (Journal of Arrhythmia, 2019)
Abstract A patient with an implantable cardioverter‐defibrillator (ICD) (Abbott®) had episodes of slow monomorphic ventricular tachycardia (VT) and his ICD was programmed with three tachycardia zones. During the follow‐up, he received an inappropriate shock. Upon interrogation (of the device), trigeminal pattern binned as ventricular sensing (VS)—VS—ventricular fibrillation (VF) was detected. VF was assumed according to binning system. When VF is present, discrimination algorithms are not available and five consecutive sinus beats are necessary to reset binning system. Catheter ablation was performed to treat VT in order to reprogram tachycardia zones.